![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\frac{x+1}{2x+6}=\frac{x+1}{2\left(x+3\right)}\)
b, \(\frac{3}{2x+6}-\frac{x-6}{2x^2+6x}=\frac{3}{2\left(x+3\right)}-\frac{x-6}{2x\left(x+3\right)}\)
\(=\frac{3x}{2x\left(x+3\right)}-\frac{x-6}{2x\left(x+3\right)}=\frac{2x+6}{2x\left(x+3\right)}=\frac{2\left(x+3\right)}{2x\left(x+3\right)}=\frac{1}{x}\)
c, \(\frac{x-x-2xy+x}{x+2y}+\frac{4xy}{4y^2-x^2}=\frac{x-2xy}{x+2y}+\frac{4xy}{\left(2y-x\right)\left(x+2y\right)}\)
\(=\frac{\left(x-2xy\right)\left(2y-x\right)}{\left(x+2y\right)\left(2y-x\right)}+\frac{4xy}{\left(2y-x\right)\left(x+2y\right)}=\frac{2xy-x^2+4xy^2+2x^2y}{\left(2y-x\right)\left(x+2y\right)}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
(2x - 3y2)3 = 8x3 - 36x2y2 + 54xy4 - 27y8 .Hệ số của x2y2 là -36
( x2 + x )2 + 4( x2 + x ) = 12
Đặt t = x2 + x
pt <=> t2 + 4t - 12 = 0
<=> t2 - 2t + 6t - 12 = 0
<=> t( t - 2 ) + 6( t - 2 ) = 0
<=> ( t - 2 )( t + 6 ) = 0
<=> ( x2 + x - 2 )( x2 + x + 6 ) = 0
<=> ( x2 - x + 2x - 2 )( x2 + x + 6 ) = 0
<=> ( x - 1 )( x + 2 )( x2 + x + 6 ) = 0
Vì x2 + x + 6 > 0 => ( x - 1 )( x + 2 ) = 0
<=> x = 1 hoặc x = -2
Vậy ...